Family matters – warm experts, older adults and social support for learning: A sequential exploratory mixed-methods approach - Martinez, Carolina; Olsson, Tobias; Viscovi, Dino (Human Technology, 2025)
The extent and quality of social support for learning provided by warm experts has received limited scholarly attention. Using a sequential exploratory mixed-methods approach, and a point of departure in theory regarding opportunities for and barriers to learning, the study starts with qualitative interviews with 22 individuals aged 70-94. Relationships between older adults and their children and grandchildren are analyzed, and experiences of opportunities and barriers for learning are identified. These findings are operationalized into items in a survey distributed to a representative sample of Sweden’s population aged 65-90 (n=1,610), to measure variations in the quantity and quality of social support for learning. Findings reveals that children are mainly engaged as warm experts, and the more frequently families meet, the more frequently support for learning takes place, and the higher the perceived quality. Age, income and education, show no relationship with the perceived quality of social support for learning.